KAJIAN IMPLEMENTASI PELUANG PRODUKSI BERSIH PADA INDUSTRI KERTAS SACK KRAFT PT X - Andes Ismayana; Tyara Puspaningrum; Mia Ulumiati Putri; Nastiti Siswi Indrasti (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Waste minimisation in paper industry activities can be done by applying cleaner production methods. The objective of this research was to study of opportunity of cleaner production implementation in sack kraft industry. These stages of research were identification of process stages, identification of problems, identification of cleaner production opportunities, feasibility analysis of technical, environmental and financial aspects, and election priority cleaner production opportunities with Exponential Comparison Method (ECM). The processes of the sack kraft production included stock preparation, sheet formation, pressing section, drying section, scrolling and cutting. These Sack Kraft Industry used 110 tonnes of cardboard afval and produced 90.742 tonnes of sack kraft, 3.65 tonnes failed paper, 2.443 tonnes scattered paper, 4.915 tonnes defected paper and 8.25 tonnes solid waste in the form of plastic and metal. The problems often had been occured were downtime machine, broken machine, solid waste production, failed paper, scattered paper, and defected paper. Recommendation of cleaner production opportunities were making pellets from solid waste as fuel substitution (PBP 0.1 years and B/C 8.31), application of Standard Operating Procedure (SOP) for machine maintenance (PBP 3.9 years and B/C 1.3), Good manufacturing practice training (PBP 0.63 years and B/C 2.58). The priority order of cleaner production using ECM was application of SOP for machine maintenance, GMP training, and making pellets as fuel substitution. Keywords: cleaner production, sack kraft, paper industry, exponential comparison method